Covid, distance education and families. The Italian case within the international survey on family support to learning processes - Sara Mori; Silvia Panzavolta; Alessia Rosa (Firenze University Press, 2022)
The COVID pandemic had countless repercussions on the family system, starting with the need to support young people in distance education training. Family and school realities have had to find new ways of relating with mutual overlap. Investigating how family members supported the learning of their children/grandchildren aged 6-16 was the aim of the international research activity coordinated by the University of Bath (UK). This contribution intends to account for the Italian data by exploring the possible relationships between the potential vulnerability factors of the pre-covid household and the activities that can be considered protective and supportive factors for households. The aim is not only to understand which competences and network systems have been activated in a period of exceptional gravity, but rather not to disperse, but on the contrary to enhance, those processes that have proved useful especially in fragile contexts.   Covid, DAD e famiglie. Il caso italiano in un'indagine internazionale sul sostegno familiare ai processi di apprendimento. La pandemia di COVID ha avuto innumerevoli ripercussioni sul sistema famigliare a partire dalla necessità di supportare i giovani nelle attività di formazione in DAD. Le realtà familiari e scolastiche hanno dovuto trovare nuove modalità di relazione con un reciproco sconfinamento. Indagare come i membri della famiglia hanno sostenuto l'apprendimento dei loro figli/nipoti dai 6 ai 16 anni è stato l'obiettivo dell'attività di ricerca internazionale coordinata dall'università University di Bath (UK).Il presente contributo intende dar conto dei dati italiani esplorando le possibili relazione tra i fattori potenziali di vulnerabilità della famiglia pre-covid e le attività che possono essere considerate fattori di protezione e di supporto per i nuclei familiari. Non si tratta soltanto di comprendere quali competenze e sistemi di rete, sono stati attivati in un periodo di eccezionale gravità, quanto piuttosto non disperdere, ma al contrario valorizzare, quei processi che si sono dimostrati utili soprattutto nei contesti di fragilità.